Dual‐analgesic loaded UHMWPE exhibits synergistic antibacterial effects against Staphylococci. Issue 4 (3rd December 2022) - Gil, Dmitry; Hugard, Shannon; Borodinov, Nikolay; Ovchinnikova, Olga S.; Muratoglu, Orhun K.; Bedair, Hany; Oral, Ebru
Abstract: Total joint arthroplasty is one of the most common surgeries in the United States, with almost a million procedures performed annually. Periprosthetic joint infections (PJI) remain the most devastating complications associated with total joint replacement. Effective antibacterial prophylaxis after primary arthroplasty could substantially reduce incidence rate of PJI. In the present study we propose to provide post‐arthroplasty prophylaxis via dual‐analgesic loaded ultra‐high molecular weight polyethylene (UHMWPE). Our approach is based on previous studies that showed pronounced antibacterial activity of analgesic‐ and NSAID‐loaded UHMWPE against Staphylococci . Here, we prepared bupivacaine/tolfenamic acid‐loaded UHMWPE and assessed its antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis . Dual‐drug loaded UHMWPE yielded an additional 1–2 log reduction of bacteria, when compared with single‐drug loaded UHMWPE. Analysis of the drug elution kinetics suggested that the observed increase in antibacterial activity is due to the increased tolfenamic acid elution from dual‐drug loaded UHMWPE. We showed that the increased fractal dimension of the drug domains in UHMWPE could be associated with increased drug elution, leading to higher antibacterial activity. Dual‐analgesic loaded UHMWPE proposed here can be used as part of multi‐modal antibacterial prophylaxis and promises substantial reduction in post‐arthroplasty mortality and morbidity.